The Cultural Geography of Luis A. Martínez: .Spaces and Identity - Sinardet, Emmanuelle (2021)
With the novel A la Costa (1904) by Luis A. Martínez, the Coastal space enters the Ecuadorian narrative. The relationship between geography and literature attests, here, to a unique cultural appropriation of coastal nature, which is transformed by the narrator’s numerous and detailed descriptions into space-values. The author studies the modalities by which spaces and landscapes are treated, between realism, costumbrismo and herderian romanticism, in order to understand the values assumed by coastal spaces; values that are not only economic, political or ideological, but also identitary and even spiritual. We observe how they gradually shape a genius that refers to a particular Volkgeist for the cultural panorama of the time, for having a sublime dimension, which also, incidentally characterizes the pictorial production of Martínez as a landscape painter.